Geotourism Destinations Online Branding Co-Creation - Tiago, Flávio; Correia, Pedro; Briciu, Victor-Alexandru; Borges-Tiago, Teresa (Sustainability, 2021)
The application of brand theory to destinations has grown in the last few decades, with the destination brand personality being a viable metaphor for creating and positioning destination brands. An often-overlooked tourism typology is geotourism; more specifically, volcanic tourism, since it can be a passive element of any tourism form or active nature tourism. However, its potential is relatively unexplored in terms of online branding. For this reason, the present study analyzes online brand image co-creation, using 300 websites related to three unique volcanic tourism destinations—Iceland, the Azores, and the Canary Islands. Three different types of sources (destination marketing organizations, commercial, and editorial websites) created these contents. The results demonstrate significant differences between the communication of the three destinations, with Iceland, where there is less aligned communication, most valuing geo elements in their communication, and the Azores, where all stakeholders communicate similar brand personality traits, displaying more aligned communication regarding brand personality. In the Canary Islands geotourism is less explored as a destination offer and is consequently less communicated. Acknowledging the different brand positioning and the parity and differentiation points among destinations with the same baseline offer—volcanic tourism—can be helpful for destination brand managers to reignite tourism and promote a unique tourism experience.